2003
DOI: 10.1046/j.1365-2842.2003.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical pilot study of the time‐dependent composition of tooth bleaching systems

Abstract: This pilot study was undertaken to determine the compositional changes in tooth bleaching materials as a function of time in vivo. Ten patients were recruited and two bleaching systems were used - one a paste and the other a gel. Each material was placed in a custom bleaching tray and worn by each patient for each of four times - 15, 30, 60 and 120 min. The material was collected and chemically analysed for water by Karl Fischer titration and titrated for carbamide peroxide by the US Pharmacopoeia method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Although there is a lack of information within the scientific literature relating to vaginal gels, this technique has been used to characterize gels used for alternative pharmaceutical applications. In a study by Wille et al [74], creep rheology was used to effectively screen tooth-bleaching materials. Similar to vaginal gels, these materials require ease of application, but should have a high viscosity at low stresses in order to be retained.…”
Section: Pharmaceutical Applications Of Rheological Methodsmentioning
confidence: 99%
“…Although there is a lack of information within the scientific literature relating to vaginal gels, this technique has been used to characterize gels used for alternative pharmaceutical applications. In a study by Wille et al [74], creep rheology was used to effectively screen tooth-bleaching materials. Similar to vaginal gels, these materials require ease of application, but should have a high viscosity at low stresses in order to be retained.…”
Section: Pharmaceutical Applications Of Rheological Methodsmentioning
confidence: 99%
“…However these studies did not include consideration of the effect of dilution by saliva. The percentage addition of artificial saliva Orthana to Zaris is based on research that showed that at 15 min in the mouth, Zaris contained as an average 20% water (11). For the whitening material Colgate Platinum Overnight (paste), artificial saliva Orthana was added to 30% Orthana, based on the research by Wille et al.…”
Section: Discussionmentioning
confidence: 99%
“…For the whitening material Colgate Platinum Overnight (paste), artificial saliva Orthana was added to 30% Orthana, based on the research by Wille et al. (11) that showed that at 15 min Colgate Platinum Overnight contained 30% water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, there were many investigations of biological factors, such as the effects of the whitening agents on filling materials, [3][4][5][6] hard tooth tissues, 7,8 and oral soft tissues. 9,10 Recently, investigations of environmental factors, such as treatment time, 11,12 comparisons of effects of bleaching gels on oral bacteria, 13 and the effects of tobacco smoking, 14 have also increased. Data on long-term observations have also been accumulated.…”
Section: Introductionmentioning
confidence: 99%